A literature review of blockchain technology applications in supply chains: A comprehensive analysis of themes, methodologies and industries. (April 2021) - Lim, Ming K.; Li, Yan; Wang, Chao; Tseng, Ming-Lang
Highlights: There is a growing interest in applying blockchain technology in supply chain operations. Research on blockchain configuration receives less attention as compared to others, such as impact and function. Discussion on sustainability is limited as compared to other themes. More research should be carried out under the themes of coordination, performance and order management. The voices of different stakeholders should be considered in academic research. Abstract: In the past few years, blockchain, the underlying technology of Bitcoin, has received considerable attention from academia and industry. It is widely accepted that blockchain technology causes disruptive changes in supply chain operations that can overcome supply chain difficulties encountered in realizing information sharing, maintaining traceability in the entire process and improving operational efficiency. However, the application of blockchain technology in the supply chain field is still in its infancy, which limits an understanding of its potential. This article uses descriptive and content analysis to review publications related to blockchain-based supply chains between 2017 and 2020 inclusive. To fully explore research on blockchain-based supply chains, four well-designed questions are proposed and addressed, namely, the value of blockchain in supply chains, the attraction of scholars to particular supply chain themes, the development of research methodologies and illustration types in adopting blockchain in supply chains, and the types of industries involved in blockchain-based supply chains. The results reveal that there is growing interest in applying blockchain technology to supply chain operations. A detailed analysis of findings is provided to identify the future opportunities of blockchain-based supply chains, including prospects for tertiary industries and concerted efforts that are necessary to explore sustainability themes. This article provides valuable information to help scholars and practitioners better determine the relevant research topics to accelerate the development of blockchain-based supply chains.